ANALISIS INVESTASI SUMATERA BARAT (PENDEKATAN ERROR CORRECTION MODELS) - Adry, Melty Roza (Program Studi Magister Ilmu Ekonomi, 2013)
ABSTRACT The purpose of this research are to analysis effect economic growth and interest rate to investment in West Sumatera in the long and short term. The data used time series data quarterly of the year 2000:1 until 2010:4. The variable used in this research are investment, economic growth, and interest rate. This research use Error Correction Model (ECM). The result of this research in long term and short term economic growth have positive influence and significant effect to investment in West Sumatera. But interest rate have negative influence and not significant effect to investment in West Sumatera Keyword: Investment, Economic Growth, Interest Rate, Error Corection Model